Pragmatic regularization of element-dependent effects in finite element simulations of ductile tensile failure initiation using fine meshes. (November 2020) - Wiegard, B.; Ehlers, S.
Abstract: For the evaluation of the structural response in accidental scenarios like ship collisions, the simulation of tensile failure initiation is inevitable. Here, one difficulty is that the process of failure initiation is a very local process, which cannot be simulated in its details at present due to the computing effort which would be required. However, there are various approaches how the failure initiation can be simplified and simulated in finite element models of large thin-walled structures. A short overview of these approaches is given. A pragmatic approach, which is suitable for relatively small elements for the simulation of failure initiation in uniaxial to biaxial stress states, is chosen within this paper for further investigations regarding the applicability for thin-walled steel structures. Exemplary simulations with solid and, in particular, shell elements are used to demonstrate how the effects of element size and other element properties can be considered in the simulation of failure initiation. The focus is also on imperfections that are relevant in simulations with small elements. For this purpose, an indentation experiment is simulated with different imperfections. Highlights: Necking is a substantial part of tensile failure of ductile steel. Necking is well simulated with small finite elements. The stress-strain curve is used to account for mesh size and element capabilities. An optimal stress-strain curve can be identified by reverse FE simulation of tests. It is important to include imperfections in fine-meshed FE models.